MAKNA PESAN PADA FILM ACTION (Analisa Semiotik pada Film Action yang Mencapai Box Office Tahun 2015) - Wijayanti Krisna (SEMIOTIKA: Jurnal Komunikasi, 2016)
This research aims to find out and explain the existence of some meaning of the message in the action movies, which reached the box office in 2015. The research is qualitative, using semiotic analysis of Roland Barthes on denotative and connotative meaning. Data obtained through observations at the box office 25 action movies circulating in Indonesia. The result showed that; there is another meaning of the message in an action movie in addition to the meaning of the message of violence. still found positive messages in an action movie like the concept of heroism, skill and technology. besides denotative meaning, there is also a connotative meaning in the meaning of violence, namely background or the reason of violence and heroism. Key words: Connotative, Denotative, Violence, Film